Analysis of radio frequency spectrum planning and allocation for the deployment of new modern broadband networks and technologies - Pasarelska, Teodora (Yearbook Telecommunications, 2024)
When analyzing the planning and distribution of the radio frequency spectrum on a global and European scale, the need to manage the radio frequency spectrum is taken into account, which is in accordance with the provisions of the Radio Regulations of the International Telecommunication Union, the decisions and recommendations of the European Commission and the Electronic Communications Committee of the European Conference by post and telecommunications. The analysis in the management of the radio frequency spectrum is also in accordance with the Bulgarian legislation, in which the principles of legality, predictability, transparency, publicity, consultativeness, equality, proportionality, neutrality in relation to the technologies used and/or the services provided and reducing the regulatory intervention to the minimum required. The basic principles of spectrum management and allocation involve a combination of technical, regulatory and organizational considerations. The purpose of writing the article is to analyze spectrum efficiency and the adaptation of spectrum management policies to evolving technologies and market dynamics.